Industrial Co-operation : the story of a peaceful revolution : being an account of the history, theory, and practice of the co-operative movement in Great Britain and Ireland - Webb, Catherine; Price, L. L.; Southern co-operative education association
ill., portr., tabl., cartes Bibliogr. p. 267-272. Index